PENGEMBANGAN STRATEGI PEMBELAJARAN AFEKTIF - Fitriani Nur Alifah (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Abstract Development of affective learning strategies, value-related strategies, which are difficult to measure, with respect to the awareness arising from within each individual. Attitudes that are a reflection of the value they have, generally confront to any situation that contains conflict or problems. The process in affective formation used in the learning strategy often uses the process of modeling. Whereas in the model of affective learning strategy using model konsiderasi, cognitive development model, value clarification techniques, cognitive moral model, and non-directive model. The characteristics in learning affective field that is about the attitudes, interests, values, moral and self-concept. In addition to aspects of cognitive and psychomotor ability formation, the formation of student attitudes is not less important is to develop an attitude so that children behave according to norms prevailing in society. Advantages: 1) Emphasize the development of thinking that involves mental and positive emotions. 2) Be able to collaborate and balance between the cognitive, affective and psychomotor domains. 3) Can form the character, attitude and mental learners mature. While Weaknesses: 1) Difficult to control because of the many factors that affect the development of one's attitude. 2) Successful formation of attitudes can not be directly evaluated, and 3) Requires long habituation. The results in implementing affective sphere in PAI learning can use several ways, namely First, Receiving. Second, Responding. Third, Valuing. Fourth, Organizing. And Fifth, Charcterization by value or value complex.